Safety control with performance guarantees of cooperative systems using compositional abstractions*. Issue 27 (2015) - Meyer, Pierre-Jean; Girard, Antoine; Witrant, Emmanuel
Abstract: In this paper, the monotonicity property is exploited to obtain symbolic abstractions, in the sense of alternating simulation, of a class of nonlinear control systems subject to disturbances. Both a centralized and a compositional approaches are presented to obtain such abstractions, from which controllers are synthesized to satisfy safety specifications and optimize a performance criterion using a receding horizon approach. Performance guarantees on the trajectories of the controlled system can be obtained with both approaches. The controller synthesis and performance guarantees are illustrated and compared on the temperature regulation in a building.